A new species of Monarda (Lamiaceae: Mentheae), M. reedii, from the eastern United States - Floden, Aaron J.; Townsend, John F. (Phytotaxa, 2026)
A new species of Monarda subg. Monarda is described, illustrated, and compared to its closest congeners. Monarda reedii sp. nov., from the Shale Barrens of Virginia and West Virginia, is compared to M. clinopodia, and also to M. bradburiana with which it has been confused, but from which it is distinctly different. Morphometric analyses using Principal Component Analysis are presented from forms of the variable M. clinopodia and samples of M. reedii. A map of its distribution is provided compared to sympatric populations of M. clinopodia.